Evaluating the performance of human resources management at Amran University in light of the requirements of sustainable development - د. عبد الجبار الطيب أمين; د. فهد صالح قاسم مغربه; د. عبد الله يحيى هادي كرشوم; أ. بسمة عبد الجليل الصالحي (University of Science and Technology, Yemen, 2023)
The study aimed at Evaluating the performance of human resources management at Amran University in light of the requirements of sustainable development. The researchers used the descriptive analytical approach. The tool consisted of a questionnaire of (37) phrases, divided into four dimensions; It was distributed to a random sample of (40) academic and administrative leaders. The results of the study showed that the tool's overall score was (3.02 out of 5); With a performance rating of (medium), and at the level of the main dimensions, the incentives and compensation dimension got the highest average (3.30), then training and development with an average of (3.12), then performance evaluation (2.90), and finally selection and appointment with an average of (2.77), all of them with an average rating (average), The results also showed that there were no statistically significant differences between the answers of the sample according to the variables (gender - educational qualification - college), and the existence of a medium relationship between human resource management and the requirements of sustainable development, based on the results; The researchers recommended developing the performance and governance of human resources, paying fair wages, salaries and incentives, developing human resources skills through training, and setting controls to measure the performance of employees according to accurate standards, in addition to proposals for complementary studies on the subject.